Modeling and Simulation of Turbulent Combustion - De, Santanu; Agarwal, Avinash Kumar; Chaudhuri, Swetaprovo; Sen, Swarnendu; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents a comprehensive review of state-of-the-art models for turbulent combustion, with special emphasis on the theory, development and applications of combustion models in practical combustion systems. It simplifies the complex multi-scale and nonlinear interaction between chemistry and turbulence to allow a broader audience to understand the modeling and numerical simulations of turbulent combustion, which remains at the forefront of research due to its industrial relevance. Further, the book provides a holistic view by covering a diverse range of basic and advanced topics-from the fundamentals of turbulence-chemistry interactions, role of high-performance computing in combustion simulations, and optimization and reduction techniques for chemical kinetics, to state-of-the-art modeling strategies for turbulent premixed and nonpremixed combustion and their applications in engineering contexts.  .
1. Tentative Title of the Chapters -- 2. Fundamentals and modelling of Turbulence - Chemistry Interactions -- 3. Development of reaction mechanisms for combustion simulations -- 4. Optimization and reduction of chemical kinetics -- 5. Turbulent Combustion simulations with HPC -- 6. Direct Numerical Simulations of Turbulent Combustion -- 7. RANS of premixed turbulent flames -- 8. Large eddy simulations of turbulent premixed combustion -- 9. Modelling of Turbulent Premixed Flames using Flamelet-Generated Manifolds -- 10. Modelling of Turbulent Premixed Flames using Conditional Moment Closure -- 11. Direct Numerical Simulations of premixed turbulent combustion: Relevance and applications to engineering computational analyses -- 12. Conditional Moment Closure Methods for Turbulent Non-Premixed Combustion -- 13. Direct Numerical Simulations of autoignition in turbulent non-premixed flames -- 14. Soot modelling in hydrocarbon flames: assessment of semi-empirical models and method of moments -- 15. Transported PDF method for MILD combustion -- 16. Large eddy simulation of nonpremixed flames using filtered mass density function approach -- 17.Multiple Mapping Conditioning Approach -- 18. Characterization of turbulent combustion systems using dynamical systems theory -- 19. Modeling of soot formation in a kerosene spray flame -- 20. Modeling and Simulations of  Turbulent Stratified Flames -- 21. Recent Progress in Turbulent Combustion Modeling of Spray Flames using Flamelet Models -- 22. Numerical simulation of turbulent combustion in internal combustion engines -- 23. On the Theory and Modelling of Flame Acceleration and Deflagration-to-Detonation Transition -- 24. Combustion in supersonic flows and scramjet combustion simulation.  .
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Engines; Engineering Thermodynamics, Heat and Mass Transfer; Engineering Fluid Dynamics; Engine Technology